IMPROVING MANIPULATIVE SKILLS AND MOTIVATION THROUGH TASK ANALYSIS AND VISUAL PROMPTING - Iwan Setiawan; Erwin Setyo Kriswanto; Lantip Diat Prasojo; Eka Sapti Cahya Ningrum; Shely Cathrin (LP2M IAI Al-Khairat Pamekasan, 2026)
This study aims to improve manipulative motor skills and learning motivation among a slow learner student in Physical Education, Sports, and Health (PJOK) through the implementation of task analysis and visual prompting strategies. Low manipulative motor skills and learning motivation were identified as problems among a seventh-grade (VII C) student at SMP Negeri 1 Rantau Pulung, necessitating an adaptive and structured instructional intervention. This study employed a Classroom Action Research (CAR) approach based on the Kemmis and McTaggart model, implemented across two cycles, each consisting of planning, action, observation, and reflection stages, with one slow learner student as the subject. Data were collected through observation, performance tests, questionnaires, and documentation, and were analyzed using descriptive quantitative and qualitative methods. The results show that manipulative motor skills improved from 43.75% in the Pre-Cycle to 81.25% in Cycle II. Learning motivation based on observation increased from 50% to 80%, while motivation based on the questionnaire increased from 60% to 84%. The implementation of task analysis and visual prompting also improved from 41.6% to 83.3%, exceeding the predetermined success criterion of ≥75%. These findings indicate that the combination of task analysis and visual prompting effectively helps slow learner students understand instructions gradually, improve motor skills, and build self-confidence and learning motivation. This study recommends the strategy as an adaptive alternative for PJOK instruction that supports inclusive education in schools.